Analysis of The Application of Good Corporate Governance and Accounting Information Systems in The Management of Bumdes - Laila Hidayati, Putri; Hwihanus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
The establishment of BUMDes in Kacongan Village is a manifestation of the Village Government's commitment to explore all existing potential and resources in order to improve the economy and welfare of the Village. However, if the commitment of the village government in establishing BUMDes is not supported by the existence of SIA and Governance capabilities in the management carried out by BUMDes administrators effectively and efficiently, then what happens is that efforts to improve the village economy towards achieving the contribution of Village Original Revenue (PAD) will certainly be very difficult to do. The study aims to determine the application of Good Corporate Governance and Accounting Information Systems in the management of BUMDes in the Village of Kacongan sumenep. The type of data used in this study is quantitative data. The author uses two informants, namely: BUMDES chairman and BUMDES secretary. Based on the results of the study, it shows that the health of BUMDES Kacongan's performance on the principles of implementing Good Corporate Governance is less than optimal in improving community welfare but it is hoped that the planned BUMDes programs will run and are expected to have a positive impact on the people of Kacongan village and the use of BUMDes Kacongan Accounting Information Systems still uses a manual recording system.